2011
DOI: 10.1371/journal.ppat.1002089
|View full text |Cite
|
Sign up to set email alerts
|

T. brucei Infection Reduces B Lymphopoiesis in Bone Marrow and Truncates Compensatory Splenic Lymphopoiesis through Transitional B-Cell Apoptosis

Abstract: African trypanosomes of the Trypanosoma brucei species are extracellular protozoan parasites that cause the deadly disease African trypanosomiasis in humans and contribute to the animal counterpart, Nagana. Trypanosome clearance from the bloodstream is mediated by antibodies specific for their Variant Surface Glycoprotein (VSG) coat antigens. However, T. brucei infection induces polyclonal B cell activation, B cell clonal exhaustion, sustained depletion of mature splenic Marginal Zone B (MZB) and Follicular B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 58 publications
5
82
0
Order By: Relevance
“…Recently, natural killer T cells and regulatory T cells have been demonstrated to influence the outcome of a trypanosome infection (41)(42)(43). Moreover, trypanosomes are also capable of reducing B lymphopoiesis and selectively destroying B-cell populations (44,45). The previous short description of immunological disorders induced by trypanosomes makes one believe that the trypanosome has developed a strategy of communication through paracrine mediators to dysregulate immune functions in a discrete manner, in addition to the powerful mechanism of VSG switching.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, natural killer T cells and regulatory T cells have been demonstrated to influence the outcome of a trypanosome infection (41)(42)(43). Moreover, trypanosomes are also capable of reducing B lymphopoiesis and selectively destroying B-cell populations (44,45). The previous short description of immunological disorders induced by trypanosomes makes one believe that the trypanosome has developed a strategy of communication through paracrine mediators to dysregulate immune functions in a discrete manner, in addition to the powerful mechanism of VSG switching.…”
Section: Discussionmentioning
confidence: 99%
“…The BM is also a site of B cell development and many infections can profoundly impact this process (47, 6974). Challenge with influenza or LCMV results in a transient decrease in pro, pre, and immature B cells in the BM, which is in part dependent on TNFα and lymphotoxin α (71, 72).…”
Section: B Cell Lymphopoiesis and Homeostasismentioning
confidence: 99%
“…7,14,15 Using either adjuvant or infection models, it has also been observed that lymphopoiesis is rapidly repressed and B cells make an exodus to the periphery mediated by reduced availability of CXCL12. 16,17 This phenomenon is thought to make way for emergency granulopoiesis, a condition of elevated granulocyte maturation that occurs to replace innate immune cells, which may have been lost in the initial onslaught against a pathogen. 18,19 However, this model does not explain how bone marrow B cells are able to produce antibody responses despite apparent instability of the population and their environment.…”
Section: Introductionmentioning
confidence: 99%